Broadband Dynamic Polarization Conversion in Optomechanical Metasurfaces - Zanotto, Simone; Colombano, Martin; Navarro-Urrios, Daniel; Biasiol, Giorgio; Sotomayor-Torres, Clivia M.; Tredicucci, A.; Pitanti, Alessandro (Frontiers in Physics, 2020)
Artificial photonic materials, nanofabricated through wavelength-scale engineering, have shown astounding and promising results in harnessing, tuning and shaping photonic beams. Metamaterials have proven to be often outperforming the natural materials they take inspiration from. In particular, metallic chiral metasurfaces have demonstrated large circular and linear dichroism of light which can be used, for example, for probing different enantiomers of biological molecules. Moreover, the precise control, through designs on demand, of the output polarization state of light impinging on a metasurface, makes this kind of structures particularly relevant for polarization-based telecommunication protocols. The reduced scale of the metasurfaces makes them also appealing for integration with nanomechanical elements, adding new dynamical features to their otherwise static or quasi-static polarization properties. To this end we designed, fabricated and characterized an all-dielectric metasurface on a suspended nanomembrane. Actuating the membrane mechanical motion, we show how the metasurface reflectance response can be modified, according to the spectral region of operation, with a corresponding intensity modulation or polarization conversion. The broad mechanical resonance at atmospheric pressure, centered at about 400 kHz, makes the metasurfaces structure suitable for high-frequency operation, mainly limited by the piezo-actuator controlling the mechanical displacement, which in our experiment reached modulation frequencies exceeding 1.3 MHz.